Enhanced near-infrared absorption for laser powder bed fusion using reduced graphene oxide. (June 2021) - Leung, Chu Lun Alex; Elizarova, Iuliia; Isaacs, Mark; Marathe, Shashidhara; Saiz, Eduardo; Lee, Peter D.
Highlights: A first successful demonstration of rGO as a near-infrared (NIR) absorber for additive manufacturing (AM) powder feedstock The NIR absorbance of rGO is 3 times better than conventional nano-carbon additives. The AM tracks containing rGO exhibit a higher density and minimum warpage compared to conventional nano-carbon additive Successful fabrication of overhang structures (directly on powder) without pre/post heat treatment enhancing AM productivity . · First in situ quantification of AM fused silica, revealing laser-matter interaction and powder consolidation mechanisms. Abstract: Laser powder bed fusion (LPBF) is a revolutionary manufacturing technology that fabricates parts with unparalleled complexity, layer-by-layer. However, there are limited choices of commercial powders for LPBF, constrained partly by the laser absorbance, an area that is not well investigated. Carbon additives are commonly used to promote near infra-red (NIR) absorbance of the powders but their efficiency is limited. Here, we combine operando synchrotron X-ray imaging with chemical characterisation techniques to elucidate the role of additives on NIR absorption, melt track and defect evolution mechanisms during LPBF. We employ a reduced graphene oxide (rGO) additive to enable LPBF of low NIR absorbance powder, SiO2, under systematic build conditions. This work successfully manufactured glass tracks with a high relative density (99.6%) and overhang features (> 5 mm long) without pre/post heat treatment. Compared to conventional carbon additives, the rGO increases the powder's NIR absorbance by ca. 3 times and decreases the warpage and porosity in LPBF glass tracks. Our approach will dramatically widen the palette of materials for laser processing and enable existing LPBF machines to process low absorbance powder, such as SiO2, using a NIR beam. Graphical abstract: Image, graphical abstract